Early Canadian Aerial Photography: The St Croix River and the International Boundary, 1921 - Werle, Dirk (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2022)
The early 1920s constitute a tentative yet pivotal period for the institution of aerial photography as an innovative surveying and mapping tool in Canada. This study focuses on vertical air photos from an experimental survey conducted in 1921 over the St Croix River boundary between Canada and the United States. Reconstituted as a plan-view mosaic, the photographs reveal a dense cluster of early twentieth century cultural-industrial features and activities that has since vanished. The study suggests that the 100-year-old set of largely unknown aerial photographs at Canada’s National Air Photo Library is a valuable source of geospatial information for historical and environmental research.